2019
DOI: 10.1029/2018ja026451
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of Earthward Propagating Flux Rope Through Re‐reconnection with Geomagnetic Field: An MMS Case Study

Abstract: Three‐dimensional global hybrid simulations and observations have shown that earthward‐moving flux ropes (FRs) can undergo magnetic reconnection (or re‐reconnection) with the near‐Earth dipole field to create dipolarization front (DF)‐like signatures that are immediately preceded by brief intervals of negative BZ. The simultaneous erosion of the southward BZ field at the leading edge of the FR and continuous reconnection of lobe magnetic flux at the X‐line tailward of the FR result in the asymmetric south‐nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 82 publications
4
12
1
Order By: Relevance
“…The magnetic pressure and tension are largely balanced at the low-beta core of the flux rope . The possibility of this type of event was later confirmed with global hybrid simulations by Lu et al (2015) and has since been observed in other studies (Breuillard et al, 2016;Man et al, 2018;Poh et al, 2019). The plasmoid-type FRs form in the cross-tail current sheet on open field lines during multiple X-line reconnection and are carried tailward by fast exhaust flows from these X-lines (Baker et al, 1996;Slavin, Lepping, et al, 2003).…”
Section: Introductionsupporting
confidence: 54%
“…The magnetic pressure and tension are largely balanced at the low-beta core of the flux rope . The possibility of this type of event was later confirmed with global hybrid simulations by Lu et al (2015) and has since been observed in other studies (Breuillard et al, 2016;Man et al, 2018;Poh et al, 2019). The plasmoid-type FRs form in the cross-tail current sheet on open field lines during multiple X-line reconnection and are carried tailward by fast exhaust flows from these X-lines (Baker et al, 1996;Slavin, Lepping, et al, 2003).…”
Section: Introductionsupporting
confidence: 54%
“…For instance, during the coalescence process, the smaller island will be eroded by the larger of the two merging islands. Similar processes are also reported in the magnetotail wherein an earthward moving flux rope is eroded when interacting with the geomagnetic field (e.g., Lu et al, 2015;Man et al, 2018;Poh et al, 2019).…”
Section: Introductionsupporting
confidence: 63%
“…In spacecraft observations, flux ropes are often identified from bipolar variations in one magnetic field component and enhancement of magnetic strength at the center. There are various observations of flux ropes in the magnetosphere (e.g., Khurana et al 1995;Slavin 2003;Yang et al 2014;Sun et al 2019;Poh et al 2019), boundary of magnetosphere (e.g., Rijnbeek et al 1984;Kawano & Russell 1997;Fear et al 2008Fear et al , 2009Akhavan-Tafti et al 2018;Hwang et al 2018;Yao et al 2020), and solar wind (e.g., Zheng & Hu 2018;BlancoCano et al 2019;Bai et al 2020). Flux ropes are also observed in magnetospheres of Mercury (Zhong et al 2020a), Mars (Briggs et al 2011), Jupiter (Sarkango et al 2021), and Saturn (Jasinski et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These kinetic-scale flux ropes may interact with one another to form larger-scale flux ropes (Daughton et al 2011), which could be manifested in spacecraft observations as entangled flux ropes (Wang et al 2017;Øieroset et al 2019;Qi et al 2020). There are also observations of ion-scale flux ropes near the ion/electron diffusion region (Wang et al 2016;Hwang et al 2018;Poh et al 2019;Dong et al 2020). The flux ropes can change in size while moving through convection, often expanding (Dong et al 2017;Akhavan-Tafti et al 2018 and sometimes contracting (Hasegawa et al 2016).…”
Section: Introductionmentioning
confidence: 99%